Assessment of competence to complete advance directives: validation of a patient centred approach. Issue 7182 (20th February 1999) - Fazel, Seena; Hope, Tony; Jacoby, Robin
Abstract: Objective : To develop a patient centred approach for the assessment of competence to complete advance directives ("living wills") of elderly people with cognitive impairment. Design :Semistructured interviews. Setting :Oxfordshire. Subjects : 50 elderly volunteers living in the community, and 50 patients withdementia on first referral from primary care. Main outcome measures : Psychometric properties of competence assessment Results : This patient centred approach for assessing competence to complete advance directives can discriminate between elderly persons living in the community and elderly patients with dementia. The procedure has good interrater ( r =0.95) and test-retest ( r =0.97) reliability. Validity was examined by relating this approach with a global assessment of competence to complete an advance directive made by two of us (both specialising in oldage psychiatry). The data were also used to determine the best threshold score for discriminating between those competent and those incompetent to complete an advance directive. Conclusion : A patient centred approach to assess competence to complete advance directives can be reliably and validly used in routine clinical practice.